Correlation analysis of tertiary lymphoid structure parameters with the prognosis of patients with locally advanced rectal cancer after neoadjuvant chemotherapy: a retrospective study - Yingjian Jiang; Chuang Zhang; Yifei Hou; Bin Zhao; Binbin Cui (World Journal of Surgical Oncology)
Abstract Background The tertiary lymphoid structures (TLSs) are positively correlated with the prognosis of many solid tumors, including colorectal cancer. However, their prognostic significance in patients with locally advanced rectal cancer (LARC) after neoadjuvant chemotherapy remains unclear. This study aimed to explore the correlation between TLS parameters and the prognosis of LARC patients receiving neoadjuvant chemotherapy. Methods This retrospective study included patients with LARC treated at the Harbin Medical University Cancer Hospital from 2012 to 2021. The quantity, area, and density of TLSs in the tumor, normal, and total tissues from surgical specimens were determined. Overall survival (OS) was calculated from surgery to death from any cause. The correlation between TLS parameters and prognosis was assessed using Kaplan-Meier survival analysis and Cox regression analysis. Multiplex immunofluorescence (mIF) staining was used to analyze TLS maturity and immune composition. Results This study included 114 patients, of whom 46.5% were over 60 years old, and 70.2% were male. TLS parameters in tumor region were smaller than those in normal and total regions (P < 0.001). A larger TLS area and higher density in the total region (HR = 0.371, P = 0.023 for area; HR = 0.250, P = 0.005 for density) were significantly associated with better OS. Moreover, a higher total-region TLS density was correlated with low carcinoembryonic antigen (CEA) levels (P = 0.028), positive responses to neoadjuvant therapy (P < 0.001), and tumor regression (P < 0.001). Subgroup analysis revealed that combining total-region TLS density with clinicopathologic features such as sex, age, cTNM stage, CEA levels, and extramural vascular invasion further stratified prognosis. Additionally, mIF analysis showed that a high TLS density was associated with a higher TLS maturity (P = 0.014); mature TLSs exhibited greater infiltration of CD20⁺ B cells and CD21⁺ follicular dendritic cells compared to non-mature TLSs. Conclusions TLS parameters, particularly TLS density, are promising prognostic biomarkers for LARC patients undergoing neoadjuvant chemotherapy. Trial registration not applicable.